Potential Hypoglycemic Property of Albiza Myriophylla Benth in Streptozotocin-Nicotinamide Induced Diabetic Rats - Sa'at, Azmah (2011)
Diabetes is a global health problem. The number of people with diabetes is increasing due to population growth, aging, urbanization, and increasing prevalence of obesity and physical inactivity. Due to the current global interest on natural or traditional remedies, the present work on Albizzia myriophylla or tebu gajah may provide another alternative to the treatment of diabetes. Initially, oral glucose tolerance test was carried out in normal rats treated with 5 mg/kg, 25 mg/kg and 50 mg/kg of aqueous bark extract of Albizia myriophylla, respectively. This was then followed by administration of the same extract, at doses of 5 mg/kg and 25 mg/kg, respectively, to normal and streptozotocinnicotinamide induced diabetic rats for 4 weeks. Subsequently, fasting blood glucose levels, changes in body weight, serum insulin, C-peptide, the liver enzymes including aspartate transaminase, alanine transaminase, the renal function test including urea and creatinine, together with cholesterol and triglyceride level were investigated in normal and diabetic rats. Additional histological findings of the kidney and liver of normal and diabetic rats were also evaluated. The results of the investigation reinforce the anti diabetic claims of Albizia myriophylla whereby significant reduction of the glucose levels were seen in diabetic rats treated with Albizia myriophylla at 5 mg/kg and 25 mg/kg for 28 days, compared to diabetic control rats. In addition, normal rats treated with Albizia myriophylla at 5 mg/kg and 25 mg/kg did not show any significant changes in the liver enzymes, renal function test and the percentage of necrotic kidney and liver cells compared to normal control rats. This may indicate the safety of consumption of Albizia myriophylla. Furthermore, Albizia myriophylla at 5 mg/kg has hepatoprotective and nephroprotective effect, as a result of better regulation of blood glucose levels, as suggested by the significant reduction in the liver enzymes, the renal function test and the liver and kidney histology after 28 days of treatment. In conclusion, Albizia myriophylla at 5 mg/kg and 25 mg/kg, respectively showed hypoglycemic activity and nephroprotective effect in streptozotocin-nicotinamide induced diabetic rats with no obvious toxicological effects on the liver and kidney. In addition, Albizia myriophylla at 5 mg/kg was able to ameliorate the liver damage induced by diabetes